2005
DOI: 10.1087/0953151052801479
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model for e‐prints and open access journal content in UK further and higher education

Abstract: A study carried out for the UK Joint Information Systems Committee examined models for the provision of access to material in institutional and subject‐based archives and in open access journals. Their relative merits were considered, addressing not only technical concerns but also how e‐print provision (by authors) can be achieved – an essential factor for an effective e‐print delivery service (for users). A ‘harvesting’ model is recommended, where the metadata of articles deposited in distributed archives ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 4 publications
(1 reference statement)
0
17
0
2
Order By: Relevance
“…This issue may diminish, however since there has been a call for mandating online academic CVs with links to full-text publications (preprints/postprints) at the institutional level to be used by promotion committees and research funders (Hitchcock et al, 2003) and the same online standardised CVs have been proposed as a rich and cheap data source for the UK Research Assessment Exercise (RAE) (Harnad, Carr, Brody & Oppenheim, 2003;Swan et al, 2005). A significant drawback for the practical use of online CVs in scientometrics, however, is that manually locating them may be difficult and time-consuming and automatic capturing online CVs by crawlers may not be possible without extensive manual data cleaning.…”
Section: Cvs In Scientometric Researchmentioning
confidence: 99%
“…This issue may diminish, however since there has been a call for mandating online academic CVs with links to full-text publications (preprints/postprints) at the institutional level to be used by promotion committees and research funders (Hitchcock et al, 2003) and the same online standardised CVs have been proposed as a rich and cheap data source for the UK Research Assessment Exercise (RAE) (Harnad, Carr, Brody & Oppenheim, 2003;Swan et al, 2005). A significant drawback for the practical use of online CVs in scientometrics, however, is that manually locating them may be difficult and time-consuming and automatic capturing online CVs by crawlers may not be possible without extensive manual data cleaning.…”
Section: Cvs In Scientometric Researchmentioning
confidence: 99%
“…C'est le risque de ne pas réussir à remplir cette archive centrale qui a surtout été dénoncé. En effet, une analyse systématique des avantages et des inconvénients de deux approches de l'auto-archivage (centrale et locale) a permis de conclure que le meilleur moyen de remplir une archive c'est par un dépôt institutionnel, suivi si on le souhaite, par une collecte centrale (SWAN et al , 2005 24 . Stevan Harnad dit clairement qu'il ne peut qu'approuver la recherche de Franck Laloë pour la meilleure inter-opérabilité possible mais il soulève les points suivants : 1) Comment obtenir le remplissage des archives avec cette centralisation?…”
Section: Hal: Centralisation Contre Décentralisation ?unclassified
“…Kemp (2005) quoted costs from ten libraries from the USA, UK, Canada and Ireland, revealing a range from around USD 7,000 to USD 1 million for repository set-up costs. Swan et al (2004) and Swan and Needham (2005) reported on the establishment and operational costs of four major institutional repositories:…”
Section: Library and Informatiomentioning
confidence: 99%
“…Annual operating costs are GBP 33,900, of which GBP 30,000 is allocated to the coordination and collection of material. Swan et al (2004) also noted that the SHERPA project experience suggested article input or 'self-archiving' costs of the order of GBP 4.46 per article. HCSTC (2004) cited cost estimates for UK higher education institutions, which included total installation costs of GBP 3,900 per institution and annual operating costs of GBP 31,300.…”
Section: Library and Informatiomentioning
confidence: 99%
See 1 more Smart Citation